The Influence of Climate Change on Vector-Borne Disease Transmission and Spread: A Case Study of Dengue and Malaria - Alamri, Amin Dakhel Bin Bakheet; Alamri, Khalid Atiah Qabih; Alfaqih, Abdullah Sarim Bin Abdullah; Alnuayri, Wejdan Ali Ahmed; Alamri, Sami Khalid Dhaifallah; Alghamdi, Abdulaziz Jamaan Saed; Alnuayri, Mousa Awad Hassan; Aljadi, Abdulrahman Khamis Abdullah; Alorabi, Fayz Mohammad Abd Alaziz; Alfaqih, Mohammed Ali (Journal of Ecohumanism, 2024)
Climate change has significantly altered global ecosystems, leading to increased risks associated with vector-borne diseases, particularly dengue and malaria. These diseases, transmitted by mosquitoes such as Aedes aegypti and Anopheles, are highly sensitive to environmental conditions, including temperature, precipitation, and humidity. Rising global temperatures, coupled with erratic weather patterns, are not only expanding the geographical range of disease vectors but also increasing their activity, abundance, and longevity. This review explores the multifaceted relationship between climate change and vector-borne disease transmission, focusing on the mechanisms by which climatic variables influence vector ecology and pathogen dynamics. Through detailed case studies of dengue and malaria, the article examines historical trends, current challenges, and future projections for disease spread in response to a changing climate. Furthermore, it highlights the importance of integrated public health strategies, early warning systems, and global cooperation to mitigate the impact of climate-sensitive diseases on vulnerable populations.